Solve y - m = 2 + 5, 3*y + 5*m - 5 = 0 for y.
5
Solve -4*v = c + 6, -34*v + 5*c = -39*v - 15 for v.
-1
Solve 2*o + 5*i = -6, -3*o + 4*i - 7 = 2 for o.
-3
Solve -t + 4*k - 9 = 0, -9 + 32 = -4*t + 3*k for t.
-5
Solve -2*f + 6*f = -3*c + 2, -c + 2*f - 6 = 0 for c.
-2
Solve -2*j + 0 = 6, 2*u = -j - 13 for u.
-5
Solve 5 = 5*g - 5*r, -22*g - 2 = -26*g + 2*r for g.
0
Solve 12 = 2*p - 4*b, -23 = -5*p + 5*b - 3 for p.
2
Solve t + 3*n + 4 = 7*n, 0 = -4*t + 2*n - 16 for t.
-4
Solve -5 - 8 = m - 3*z, 5*m + 5 = -5*z for m.
-4